Legal Problems of the Formation and Development of the Institute of Environmentally Unfavourable Territories - NURUTDINOVA, Ainura Zharylgasynkyzy; BEKISHEVA, Sabigul Dzhanabaevna (Journal of Environmental Management and Tourism, 2020)
The legal regime of environmentally unfavourable territories is studied in the article. Nowadays, more and more areas of the territory of Kazakhstan are exposed to unfavourable impact on the environment due to the increasing influence of developing scientific and technical progress. These activities do not only harm environmental systems and individual natural resources but also complicate and sometimes make it impossible for citizens to live in these areas. Such areas of the territory need to be restored, the damage should be compensated, and the inconveniences of human habitation should be compensated. Thus, there is a need to establish special legal regimes governing the respective responsibilities of those who carry out activities that degrade the environmental situation in these areas, the authorities, and the rights of citizens living in these areas. The objective of the presented study is to analyze the legislation regulating the legal regime of environmentally unfavourable territories in the Republic of Kazakhstan and the international experience of such regulations. As a result of the research, the authors conclude that it is necessary to develop a comprehensive legal regulation to address most of the issues of ensuring the restoration of environmentally unfavourable areas, compensation for environmental damage, and reimbursement to the population.